PENGARUH DUKUNGAN KELUARGA TERHADAP KEPATUHAN PASIEN MENJALANI PERAWATAN LUKA ULKUS DIABETIK - Julidia Safitri Parinduri; Sri Dewi Br Siregar; Nanda Sukma Khairunnisa; Isni Hijriana; Hendry Mendrofa (Jurnal Keperawatan Priority, 2023)
Diabetic ulcers are open sores on the skin layer to the dermis, which usually occur on the soles of the feet. Wounds that arise in DM patients due to complications of microangiopathy and macroangiopathy. Peripheral neuropathy will cause loss of sensation in the distal area of ​​the foot. The length of time a person suffers from DM will cause microangiopathic complications so diabetic neuropathy will cause ulcers on the feet. This study aims to determine the relationship between family support in the healing process of diabetic ulcers with patient compliance in undergoing treatment at the Asri Wound Care Center clinic in Medan using a descriptive correlation research design with a cross-sectional design. The sample in this study was 36 respondents using an accidental sampling technique. The results of the Spearman rank test (rho) with a p-value = 0.004 with a coefficient value of 0.467 then p-value <a (0.000 <0.05), meaning that there is a relationship between family support in the healing process of diabetic ulcers with patient compliance in undergoing treatment at the Asri Wound clinic. Care Center Medan. For education, it is expected that educational institutions can increase the knowledge of students at the institution regarding the importance of family support in the process of healing diabetic ulcers with patient compliance in undergoing treatment.